The Flood Limitation Compliance and Quality of Life Patients with Chronic Kidney Disease in The Hemodialysis Room Of PKU Muhammadiyah Yogyakarta Hospital - Siti Fadlilah (Poltekkes Kemenkes Yogyakarta, 2020)
Fluid compliance is one of the therapies that patients can do to control the amount of fluid that enters in accordance with the amount of fluid that comes out. Fluid restriction therapy is to add urine out for 24 hours + 500 ml. Fluid restriction is done to prevent various complications including excess fluid volume and shortness of breath. These complications can reduce the quality of life and even cause death. This study was to determine the relationship of age, sex, education and occupation with adherence to fluid restrictions and quality of life of patients with chronic kidney failure in the hemodialysis room at PKU Muhammadiyah Hospital Yogyakarta. This type of research is analytic quantitative research with a cross sectional research design. Research respondents were 114 patients with chronic kidney failure who underwent hemodialysis therapy with technique accidental sampling. The research instrument used a questionnaire. The result of adherence to fluid restriction patients with chronic renal failure most respondents in the category of non-compliance 63 people (55.3%) and the quality of life of the most respondents enough categories 70 people (61.4%). Analysis of the relationship between age and education with adherence to fluid restriction obtained p-values ??of 0.021 and 0.005. Analysis of the relationship between sex and occupation with adherence to fluid restriction obtained p-values ??of 0.592 and 0.065. The results of bivariate analysis between age, sex, education, and compliance with fluid restriction with quality of life obtained p-values ??of 0.001; 0.003; 0,000; 0.015; 0,000. There is a relationship between age and education with fluid restriction compliance, while gender and occupation have no relationship with fluid restriction compliance. There is a relationship between age, gender, education, and adherence to fluid restrictions with the quality of life of patients with chronic renal failure in the hemodialysis room at PKU Muhammadiyah Hospital in Yogyakarta. Fluid compliance is one of the therapies that patients can do to control the amount of fluid that enters in accordance with the amount of fluid that comes out. Fluid restriction therapy is to add urine out for 24 hours + 500 ml. Fluid restriction is done to prevent various complications including excess fluid volume and shortness of breath. These complications can reduce the quality of life and even cause death. This study was to determine the relationship of fluid restriction adherence with the quality of life of patients with chronic kidney failure in the hemodialysis room at PKU Muhammadiyah Hospital in Yogyakarta. This type of research is analytic quantitative research with a cross sectional research design. Research respondents were 114 patients with chronic kidney failure who underwent hemodialysis therapy with technique accidental sampling. The research instrument used a questionnaire. The result of adherence to fluid restriction patients with chronic renal failure most respondents in the category of non-compliance 63 people (55.3%) and the quality of life of the most respondents enough categories 70 people (61.4%). Analysis of the relationship between compliance to fluid restriction with quality of life obtained a p-value of 0,000, with an alpha value of 0.05. There is a significant relationship between compliance with fluid restriction with the quality of life of patients with chronic kidney failure in the hemodialysis room at PKU Muhammadiyah Hospital in Yogyakarta.